2022
DOI: 10.1002/andp.202200235
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation and Improvement of Autofocusing Properties for Circular Butterfly Beams

Abstract: A new class of (2+1)‐dimensional circular butterfly beams (CBBs) is first demonstrated based on high‐dimensional butterfly catastrophes. The intensity of CBBs increases abruptly by two orders of magnitude right before they propagate to the focal plane, implying that they possess an abruptly autofocusing (AAF) ability induced by accelerating properties. The autofocusing performance can be further improved by introducing vortices. Owing to the flexibility of high‐dimensional catastrophes, butterfly beams exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Focused beams can be used to manipulate small particles and improve the signal-to-noise ratio for free-space optical links [1,2]. Researches have shown that some beams have abrupt auto-focusing properties, such as circular Airy beams (CABs) [1,3], circle Pearcey beams [4,5], circle Olver beams [6], and so on [7][8][9]. It is worth mentioning that the CABs have attracted a lot of attention due to their auto-focusing property.…”
Section: Introductionmentioning
confidence: 99%
“…Focused beams can be used to manipulate small particles and improve the signal-to-noise ratio for free-space optical links [1,2]. Researches have shown that some beams have abrupt auto-focusing properties, such as circular Airy beams (CABs) [1,3], circle Pearcey beams [4,5], circle Olver beams [6], and so on [7][8][9]. It is worth mentioning that the CABs have attracted a lot of attention due to their auto-focusing property.…”
Section: Introductionmentioning
confidence: 99%